A Comparison of Antimetastatic Activity between Nerium indicum and Cinnamomum burmannii on 4T1 Cells - Beni Lestari; Laeli Muntafiah; Ziana Walidah; Riris Istighfari Jenie (Indonesian Society for Cancer Chemoprevention, 2017)
Metastatic process becomes a major problem in advanced cancer cases. Natural compounds found in several plants in Indonesia have a potency to be developed as chemoterapeutic agent which are targeted to metastatic process. Jure leaves (Nerium indicum) which contain oleandrin and cinnamaldehyde in cinnamon bark (Cinnamomum burmannii) reported to have cytotoxic activity on several cancer cells, but their activities on metastasic process have never been explored. This research aims to reveal and to compare their anti-metastatic effect toward 4T1 breast cancer cells. The cytotoxicity of jure leaves extract (JLE) and cinnamon essential oil (CEO) was obtained by MTT assay. Metastatic process mainly on cell migration was examined by scratch wound healing assay while MMP-9 expression that described the invassion process was observed by gelatin zymography assay. Molecular interaction between their active compounds and MMP-9 receptor was predicted by molecular docking. The result showed that treatment with JLE and CEO inhibited the growth of 4T1 cells with IC50 value of 125 µg/mL and 2.5 µg/mL, respectively. In addition, JLE performed inhibitory effect of cell migration better than CEO. Meanwhile, both JLE and CEO decreased MMP-9 protein expression. Thus, JLE and CEO have potentials to be developed as an anti-metastatic agent and JLE could be more effective.Key words: Nerium indicum, Cinnamomum burmannii, anti-metastasis, scratch assay, gelatin zimography